Predicting new-onset diabetes after minimally invasive subtotal distal pancreatectomy in benign and borderline malignant lesions of the pancreas. Issue 51 (December 2017) - Hwang, Ho Kyoung; Park, Jiae; Choi, Sung Hoon; Kang, Chang Moo; Lee, Woo Jung
Abstract : Abstract: The purpose of this study was to evaluate the time-dependent probability and risk factors of pancreatogenic diabetes mellitus (PDM) in patients who underwent minimally invasive subtotal distal pancreatectomy. Changes in glucose metabolic consequence of 34 patients (laparoscopic: 31, robotic: 3) who underwent surgery from December 2005 to December 2014 were estimated by assessing impaired fasting glucose, PDM, and PDM-free time analysis. A total of 22 patients showed glucose intolerance, including 13 (38.2%) with impaired fasting glucose and 9 (26.5%) with PDM. The median onset time of PDM was 6.8 months (range 5.3–13.2 months). The PDM-free time probability according to time interval was 94.1% (6 months), 75.9% (12 months), and 72.6% (18 months). It was shown that body mass index>23 kg/m 2 (49.9 vs 87.9 months, P  = .020) and preoperative cholesterol >200 mg/dL (40.9 vs 85.2 months, P  = .003) adversely influenced PDM-free time. Preoperative cholesterol >200 mg/dL (hazard ratio = 6.172; 95% confidence interval, 1.532–24.865; P  = .010) was significantly associated with short PDM-free time in Cox proportional hazards model. Patients with high cholesterol levels and high BMI should be closely monitored for the development of PDM.